Comparison between manual and finite element analysis of RC wall in various length to height ratio / Mohd Shahrul Azhary Mohamad - Mohamad, Mohd Shahrul Azhary (2007)
RC walls is an element of the building that shows a different behavior of stress, strain and crack pattern compared with other element such as beam and column. Reinforced concrete (RC) walls are commonly used today and most efficient when they align vertically and are supported on foundation walls or footings. When shear walls do not align, other parts of the building will need additional strengthening. This study is carried out to interpret the behavior and characteristic of the RC wall. The study are focus on the design and analysis of the RC wall by using three method, manual calculation using Euro Code system, and Finite Element method in linear and non linear analysis and laboratory work. The RC walls with web reinforcement will built in the same size with wire mesh. Deform bars having yield strength 250 N/mim for diameter 6mm. Ordinary Portland cement with sand and aggregate are used for concrete mix to RC wall structure. The characteristic strength concrete use for develop RC wall in the laboratories are 30N/mm2. The load are applied in point load and uniform distributed load to the specimen until the specimen fail in strength. With different type of loading applied to the specimen, the characteristic and behavior of RC wall are study according to the mode of failure, crack pattern, ultimate load and stress field method. The results are compared with Finite Element Method using LUSAS software and continue using simulation to determine the effect of length to height ratio for RC wall. From comparison between laboratory work and simulation, according to mode of failure and crack pattern, there are three type of failure occur to the RC wall, failure at support, failure at loading transfer and failure according to real failure that proposed by Leonhardt and Wather. Beside that, using three point testing give higher ultimate load than using four point testing. By changing the length to height ratio, the result in ultimate load and displacement of RC wall are increases according increasing the height of RC wall.